The development of a measure of maternal cognitive sensitivity appropriate for use in primary care health settings. (3rd September 2014) - Prime, Heather; Browne, Dillon; Akbari, Emis; Wade, Mark; Madigan, Sheri; Jenkins, Jennifer M.
Abstract : Background: Parental responsivity is important to children's cognitive and socioemotional development, yet is under‐represented in primary healthcare, because the measurement is specialized and time‐consuming. Methods: The current study developed a measure of maternal cognitive sensitivity (CS), which uses impressionistic ratings based on brief observations of parent–child interaction when children are 3 years old. Results: Using data from a longitudinal cohort (Time 1, N = 501), the CS measure had good psychometric properties, was significantly related to a gold‐standard maternal responsivity measure, and was predicted by the same socio‐demographic factors predictive of other measures of parental responsivity. Finally, a well‐established pathway from socioeconomic risk (child age 2 months) to compromised parenting (child age 3 years) to negative child outcome (child age 4.5 years) was demonstrated with CS as the mediator. Conclusion: The maternal CS measure is brief, can be easily trained, and takes 8 min to administer and code, making it potentially useful in primary healthcare settings.